Involvement in self-care of a patient with type 2 diabetes aged 60-80 - Ewelina Bąk; Renata Potoczna; Bogusława Kupczak-Wiśniowska (Kazimierz Wielki University, 2024)
Introduction: Self-care is an indispensable element of the treatment of type 2 diabetes, it involves the independent implementation of multidimensional activities that allow you to maintain proper glucose levels and reduce the risk of complications. Materials and methods: The study was conducted on a group of 100 patients (including 56 women and 44 men) at the Health Clinic in Zembrzyce in the period from August 10, 2019 to October 30, 2019. The study was conducted using the diagnostic survey method. The research tools included: a self-report questionnaire consisting of a sociodemographic and clinical part and the Self-Care Inventory in Diabetes (SCODI). Results: It was shown that greater independence in self-care regarding health behaviors, health control, glucose control and self-confidence were significantly higher in patients without addictions. Conclusions: Involvement in self-care in the study population was higher among patients with secondary and higher education, and in patients without addictions, with normal body weight and underweight and treated with diet, tablets and insulin.